The Labour Market Effect of Immigration: Accounting for Effective Immigrant Work Experience in New Zealand - Michael M. H. Tse; Sholeh A. Maani (Institute of Labor Economics (IZA), 2016)
This guide, updated for the 2016-17 job market season, describes the U.S. academic market for new Ph.D. economists and offers advice on conducting an academic job search. It provides data, reports findings from published papers, describes practical details, and includes links to online resources. Topics addressed include: preparing to go on the market; applying for academic jobs; the JOE Network, which is the AEA's electronic clearinghouse for the job market; signaling; interviewing at the ASSA meetings; campus visits; the secondary market scramble; offers and negotiating; getting off to a good start as an assistant professor; diversity; and dual job searches.
Keywords: J61; J62; J31; J3; J24; 330; human capital; immigrants; effective work experience; wage effects; employment effects; regions